2003
DOI: 10.1016/s0006-3495(03)74657-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Surface Tension and Osmotic Pressure on the Interfacial Hydration of a Fluid Phospholipid Bilayer

Abstract: The effects of three so-called kosmotropic solutes, namely, betaine, sucrose, and choline chloride on 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine large unilamellar vesicles, were studied by measuring the generalized polarization (GP) for the fluorescence emission of the membrane partitioning probe Laurdan. The latter has been shown to be sensitive to the depth of water penetration into phospholipid bilayers. At equal osmotic pressures the three solutes produced different increments in GP, with a qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 57 publications
1
53
0
Order By: Relevance
“…Other stabilizing consequences of sugar binding have been put forward, and in this paper, we collectively refer to this interpretation as the "interaction hypothesis." In contrast to this, other works have concluded that the sugars are preferentially expelled from the hydration zone and that their effect on the membrane is exerted indirectly by the local osmotic imbalance and the concomitant increase in interfacial free energy (25)(26)(27)(28)(29)(30). We call this the "exclusion hypothesis.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Other stabilizing consequences of sugar binding have been put forward, and in this paper, we collectively refer to this interpretation as the "interaction hypothesis." In contrast to this, other works have concluded that the sugars are preferentially expelled from the hydration zone and that their effect on the membrane is exerted indirectly by the local osmotic imbalance and the concomitant increase in interfacial free energy (25)(26)(27)(28)(29)(30). We call this the "exclusion hypothesis.…”
mentioning
confidence: 81%
“…This ubiquitous correlation is explained by a preferential expulsion or exclusion that increases the interfacial free energy and thus promotes the stability of lipid phases with low water accessible areas. The exclusion hypothesis has been supported by some spectroscopic evidence (28), and recently both small-angle scattering studies (36,38) and vapor pressure measurements (39) have provided direct evidence for a partial depletion of sugar in the hydration zone of lipid bilayers. Several aspects of the exclusion hypothesis were recently discussed by Lenné et al (40) who concluded that "sugars partition away from the phospholipid headgroups, rather than inserting between the headgroups.…”
mentioning
confidence: 84%
“…A higher osmolarity of the extravesicular environment yields vesicles with a higher membrane order and thus a higher degree of lipid packing. 36 …”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have focused on the difference of how kosmotropic and chaotropic solutes interact with lipid membranes [122][123][124]. Kosmotropes deplete the solution at the interface and increase the interfacial tension whereas chaotropes accumulate in the interface and decrease surface tension [125]. The changes in the structure of water due to these types of chemicals can be attributed to alterations in the hydrogen bonding network of water [126,127].…”
Section: Chemical Inhibition Of the Interdigitated Gel Phasementioning
confidence: 99%